Evil star - Horowitz, Anthony (London : Walker Books, 2006)
Having locked the Ravenś gate, fourteen-year-old Matt travels to Peru where he meets the second of the five gatekeepers and works with him to try to stop the opening of a second gate somehow related to the Nazca Lines.
Keywords: Incas -- Fiction; Peru -- Fiction; Supernatural -- Fiction